Building a general and data-efficient convolutional neural network-based model for fast urban flow estimation - J. Calafell; J. Bustillo; J.M. Armengol; S. Gómez; F. Ramirez-Javega; O. Lehmkuhl (Building and Environment, 2026)

S20-03 AnthroDrugs-Tox: Personalized Toxicology through Population Genetics - S. Perera del Rosario; L.E. Carpio; E. Serrano-Candelas; J. Garcia Calleja; L. Vilà-Valls; E. Bosch; F. Calafell; R. Gozalbes Botella (Toxicology Letters, 2025)

Mitochondrial DNA reveals a strong phylogeographic structure in the badger across Eurasia - J. MARMI; F. LÓPEZ‐GIRÁLDEZ; D. W. MACDONALD; F. CALAFELL; E. ZHOLNEROVSKAYA; X. DOMINGO‐ROURA (Molecular Ecology, 2006)
The badger, Meles meles , is a widely distributed mustelid in Eurasia and shows large geographic variability in morphological characters whose evolutionary significance is unclear and needs to be contrasted with molecular data. We sequenced 512 bp of the mitochondrial DNA control region in 115 Eurasian badgers from 21 countries in order to test for the existence of structuring in their phylogeography, to describe the genetic relationships among their populations across its widespread geographic range, and to infer demographic and biogeographic processes. We found that the Eurasian badger is divided into four groups regarding their mitochondrial DNA: Europe, Southwest Asia, North and East Asia, and Japan. This result suggests that the separation of badgers into phylogeographic groups was influenced by cold Pleistocene glacial stages and permafrost boundaries in Eurasia, and by geographic barriers, such as mountains and deserts. Genetic variation within phylogeographic groups based on distances assuming the Tamura–Nei model with rate heterogeneity and invariable sites ( d T‐N range: 3.3–4.2) was much lower than among them ( d T‐N range: 10.7–38.0), and 80% of the variation could be attributed to differences among regions. Spatial analysis of molecular variance ( samova ), median‐joining network, and Mantel test did not detect genetic structuring within any of the phylogeographic groups with the exception of Europe, where 50% of variation was explained by differences among groups of populations. Our data suggest that the European, Southwest Asian, and North and East Asian badgers evolved separately since the end of Pliocene, at the beginnings of glacial ages, whereas Japanese badgers separated from continental Asian badgers during the middle Pleistocene. Endangered badgers from Crete Island, classified as Meles meles arcalus subspecies, were closely related to badgers from Southwest Asia. We also detected sudden demographic growth in European and Southwest Asian badgers that occurred during the Middle Pleistocene.

Genetic distances and microsatellite diversification in humans - F. Calafell; A. Pérez-Lezaun; J. Bertranpetit (Human Genetics, 2000)

Mitochondrial DNA variation and the origin of the Europeans - D. Comas; F. Calafell; E. Mateu; A. Prez-Lezaun; E. Bosch; J. Bertranpetit (Human Genetics, 1997)